PKM Meningkatkan Volume Penjualan Melalui E-Commerce Pada Makanan Olahan Gipang Dangdeur di Kelurahan Gelam: Pengabdian - Asnawi; Mochamad Arief Ramadani; Nada Nabilah; Rasendriya Azel Qodama; Siti Nunu Parwati; Wita Martianingsih (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
it cannot be denied that the digital era has developed greatly in today's society. All fields are required to be able to utilize technology, including the MSME sector. In fact, all groups from children to the elderly are already technologically literate because the world has begun to evolve. This allows people to enjoy and follow existing technological developments, including the fields of social media and e-commerce which cannot be separated from the Internet. Advertising media that uses internet technology or other technological media is usually called e-commerce which has the advantage of being able to carry out buying and selling activities between sellers, and applications that use internet technology to make online purchases. Usually the e-commerce that is widely used by business people is Shopee and TikTok. An attractive and easy to understand website appearance is an important thing that people must pay attention to in e-commerce. Currently, small and medium businesses are starting to realize that people are increasingly interested in shopping online, because consumers have also started to follow developments in digital technology and no longer need to go to shopping places to get the goods they want, what is offered in e-commerce is no less competitive.